2010
DOI: 10.1111/j.1462-5822.2010.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii protease TgSUB1 is required for cell surface processing of micronemal adhesive complexes and efficient adhesion of tachyzoites

Abstract: SummaryHost cell invasion by Toxoplasma gondii is critically dependent upon adhesive proteins secreted from the micronemes. Proteolytic trimming of microneme contents occurs rapidly after their secretion onto the parasite surface and is proposed to regulate adhesive complex activation to enhance binding to host cell receptors. However, the proteases responsible and their exact function are still unknown. In this report, we show that T. gondii tachyzoites lacking the microneme subtilisin protease TgSUB1 have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 50 publications
6
87
0
3
Order By: Relevance
“…1, A-C). The heteronuclear 15 N NOE showed that NOE values for the C-terminal six residues are significantly lower than for the main globular domain (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1, A-C). The heteronuclear 15 N NOE showed that NOE values for the C-terminal six residues are significantly lower than for the main globular domain (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…The protein fractions were pooled together, concentrated to ϳ500 M, and exchanged into an NMR buffer (25 mM KH 2 PO 4 , pH 7.2, 100 mM NaCl). 15 N, 13 C-labeled samples of WT MIC5 were produced in minimal medium containing 0.07% 15 NH 4 Cl and 0.2% 13 C 6 -glucose. Solution Structure Determination of TgMIC5-Backbone and side chain assignments were completed using our in-house, semiautomated assignment algorithms and standard triple-resonance assignment methodology (19).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chrompodellids also share an expansion in subtilisin proteases (SI Appendix, Fig. S7), which are secreted from micronemes and important for adhesion to host cell during infection (40). Lastly, two groups of proteins are uniquely shared between apicomplexans and their closest relatives and potentially linked to shared morphologies (SI Appendix, Table S6).…”
Section: /Namentioning
confidence: 99%